2016
DOI: 10.1016/j.ydbio.2016.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Bhlhb5::flpo allele uncovers a requirement for Bhlhb5 for the development of the dorsal cochlear nucleus

Abstract: Auditory information is initially processed in the cochlear nuclei before being relayed to the brain. The cochlear nuclei are subdivided into dorsal, anterior ventral, and posterior ventral domains, each containing several subtypes of neurons that are thought to play discrete roles in the processing of sound. However, the ontogeny of these neurons is poorly understood, and this gap in knowledge hampers efforts to understand the basic neural circuitry of this nucleus. Here, we reveal that Bhlhb5 is expressed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Spatiotemporal fate mapping for Neurog1-expressing cells with Neurog1-Cre BAC (bacterial artificial chromosome) transgenic mice has shown Neurog1 to be expressed in the CN, LL, and IC, and throughout the cortex and most of the thalamus (Kim et al 2011), but the mode of action of neurog1 in these brainstem auditory nuclei has yet to be investigated. Finally, the gene encoding the proneural bHLH transcription factor bhlhb5 is expressed in SGNs from E10.5 (Brunelli et al 2003), in the dorsal CN from E12 (Cai et al 2016), and in several primary sensory cortices, including the AC, soon after birth (Joshi et al 2008). Bhlhb5 knockout mice have very small numbers of dorsal CN neurons, such as cartwheel cells and unipolar brush cells (Cai et al 2016).…”
Section: B) Genes Involved In Both Cochlea and Auditory Hindbrain Devmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatiotemporal fate mapping for Neurog1-expressing cells with Neurog1-Cre BAC (bacterial artificial chromosome) transgenic mice has shown Neurog1 to be expressed in the CN, LL, and IC, and throughout the cortex and most of the thalamus (Kim et al 2011), but the mode of action of neurog1 in these brainstem auditory nuclei has yet to be investigated. Finally, the gene encoding the proneural bHLH transcription factor bhlhb5 is expressed in SGNs from E10.5 (Brunelli et al 2003), in the dorsal CN from E12 (Cai et al 2016), and in several primary sensory cortices, including the AC, soon after birth (Joshi et al 2008). Bhlhb5 knockout mice have very small numbers of dorsal CN neurons, such as cartwheel cells and unipolar brush cells (Cai et al 2016).…”
Section: B) Genes Involved In Both Cochlea and Auditory Hindbrain Devmentioning
confidence: 99%
“…Finally, the gene encoding the proneural bHLH transcription factor bhlhb5 is expressed in SGNs from E10.5 (Brunelli et al 2003), in the dorsal CN from E12 (Cai et al 2016), and in several primary sensory cortices, including the AC, soon after birth (Joshi et al 2008). Bhlhb5 knockout mice have very small numbers of dorsal CN neurons, such as cartwheel cells and unipolar brush cells (Cai et al 2016). However, the functional roles of Bhlhb5 in the SGNs and the AC remain to be determined.…”
Section: B) Genes Involved In Both Cochlea and Auditory Hindbrain Devmentioning
confidence: 99%
“…Chief among those is Ptf1a, a bHLH transcription factor that is essential for cerebellar (Pascual et al, 2007) (Millen et al, 2014) and dorsal cochlear nucleus development (Fujiyama et al, 2009) but other bHLH genes play a role as well (Cai et al, 2016). In addition, to be relevant for the formation of nuclei or brain areas, Ptf1a also plays an essential role in cell fate determination within a given nucleus defining excitatory and inhibitory neurons (Iskusnykh et al, 2016) Beyond formation of entire nuclei, several genes are now emerging that interact to define different cell types in different brainstem nuclei important for their normal function (Nothwang, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For the mouse, the Cre/loxP system is the most widely used SSR for advanced genome engineering 32 . But with increased sophistication of experimental designs, the Dre/rox system and enhanced versions of Flp recombinase are now also routinely used in mice, with a number of Dre and Flp-deleter strains 16 , 17 , 22 , 43 , 44 and tissue-specific Dre-drivers 10 , 26 , 45 as well as tissue-specific Flp-drivers 46 51 demonstrating the utility of these enzymes in vivo . As an example, combinatorial use of tissue specific Dre and Cre recombinases in mice revealed that liver vasculature arises from the endocardium 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a panel of different recombinase-reporter strains for Cre, Flp and Dre have been reported 22 , 37 , 38 , 40 , 62 . The number of Cre-driver mice is constantly increasing 5 , 6 and a number of tissue-specific Dre-drivers 10 , 45 as well as tissue-specific Flp-drivers 46 51 also already exist. The prediction is that more will be made and that Vika will likely follow this trend.…”
Section: Discussionmentioning
confidence: 99%